Cross‐Talk between CD31 and the Signaling Lymphocytic Activation Molecule–Associated Protein during Interferon‐γ Production against Mycobacterium tuberculosis - Quiroga, María Florencia (2007)
Effective host defense against tuberculosis requires Th1 cytokine responses. We studied the regulation of interferon (IFN)-γ production during tuberculosis by investigating the role of CD31, a receptor that attenuates T cell receptor signals. After antigen stimulation, CD3+CD31+ blood lymphocytes decreased in healthy donors and in tuberculosis patients with robust Th1 responses to Mycobacterium tuberculosis and IFN-γ was secreted only by CD31- T cells. In contrast, in patients with weak Th1 cytokine responses to M. tuberculosis, the level of CD3+CD31+ lymphocytes was increased and IFN-γ production was low. Furthermore, the inverse relationship between CD31 expression and IFN-γ production was in contrast to signaling lymphocytic activation molecule (SLAM) expression, an IFN-γ inducer in tuberculosis. Interestingly, CD31 bound to SLAM-associated protein (SAP), an IFN-γ inhibitor in tuberculosis, and when CD31 and SAP were coexpressed in lymphocytes, their association inhibited the IFN-γ response to M. tuberculosis. Thus, CD31, when binding to SAP, interferes with Th1 responses, suggesting that CD31 has a key regulatory role in the signaling pathway(s) leading to the IFN-γ response to M. tuberculosis.